Analisis Kapasitas dan Pemberdayaan Masyarakat di Desa Wisata Bagot, Samosir - Sihombing, Bernadet; Suprihanto, John (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
New tourist villages generally face general problems such as a lack of understanding about tourism and community empowerment, so the community's lack of ability to cultivate the potential of the region. By equipping themselves with the CCB concept of good management can maximize the performance of tourist villages. The problems that arise related to the capacity faced by the Bagot Tourism Village. The purpose of this study is to identify the capacity of individuals, organizations, and communities in the Bagot Tourism Village and to evaluate the capacity for community empowerment in the Bagot Tourism Village. A qualitative approach was used in this study by conducting in-depth interviews with informants who benefited directly and indirectly from the Bagot Tourism Village. The results of the analysis that has been carried out that it was found that the Bagot Tourism Village at the individual, organizational and community level has a moderate capacity. The evaluation carried out on the empowerment and capacity of the Bagot Tourism Village shows that the social empowerment and psychological empowerment of the Bagot Tourism Village community are in the high category and political empowerment which is felt to be in the medium category. Keywords : Community capacity; Empowerment; Tourism village